Part A: RNA Therapeutics. Development and challenges in nanoparticle delivery/ Part B: Synthesis and characterisation of supramolecular polyplexes for mRNA delivery - Vasudevan, Akshaya (2024)
Part A: With the approval of mRNA vaccines for the COVID-19 pandemic, RNA therapeutics have gained significant attention. They can be used for treatment, prophylaxis, or amelioration of diseases such as cancer, infectious diseases, as well as rare genetic disorders. With a suite of RNAs and delivery systems at our disposal a tailored approach can be designed for any target condition. Despite this, there are few clinically approved RNA treatments. In practice, RNA therapeutics face several challenges primarily enzymatic degradation, immunogenicity, low cellular uptake, and less endosomal release each of which must be mitigated before clinical approval is achieved. This review introduces the types of RNA, their delivery systems, and the challenges faced in RNA therapeutics. It also briefly discusses current advancements in designing RNA nanoparticles.